Feto-Maternal Trafficking of Exosomes in Murine Pregnancy Models - Sheller-Miller, Samantha; Lei, Jun; Saade, George; Salomon, Carlos; Burd, Irina; Menon, Ramkumar (Frontiers in Pharmacology, 2016)
Timing and initiation of labor are well-orchestrated by signals communicated between the fetal and maternal compartments; however, how these signals are communicated is not completely understood. Fetal exosomes, intercellular signaling vesicles, may play a key role in the process. The objective of this study was to evaluate exosome trafficking in vivo from fetal to maternal compartments. Pregnant CD-1 mice were intra-amniotically injected on gestational day 16 and 17 with exosomes isolated from primary human amnion epithelial cells fluorescently labeled with the lipophilic dye 1,1-dioctadecyl-3,3,3,3-tetramethylindotricarbocyanine iodide (DiR). All our analyses were performed on samples collected on Day 18. After 24 hours, mice were imaged using Bruker MS FX PRO In Vivo Imager and tissues were collected. In vivo imaging of mouse showed fluorescence in the uterus, on the exosome-injected side whereas the uterine tissues from the uninjected side and saline and dye alone injected animals remained negative. Histological analysis of placenta showed exosome migration from the fetal to the maternal side of the placenta. Fluorescence released from exosomes was seen in maternal blood samples as well as in maternal uterus and kidneys. This study demonstrates that exosomal cargo can be carried through systemic route from the fetal to the maternal side of the uterine tissues during pregnancy, supporting the idea that fetal signals can be delivered via exosomes.